Increasing availability of ω‐3 fatty acid in the early‐life diet prevents the early‐life stress‐induced cognitive impairments without affecting metabolic alterations. Issue 4 (23rd January 2019) - Yam, Kit‐Yi; Schipper, Lidewij; Reemst, Kitty; Ruigrok, Silvie R.; Abbink, Maralinde R.; Hoeijmakers, Lianne; Naninck, Eva F. G.; Zarekiani, Parand; Oosting, Annemarie; Van Der Beek, Eline M.; Lucassen, Paul J.; Korosi, Aniko
ABSTRACT: Exposure to early‐life stress (ES) is associated with cognitive and metabolic deficits in adulthood. The role of early nutrition in programming these long‐term effects is largely unknown. We focused on essential ω‐3 and ω‐6 long‐chain polyunsaturated fatty acids (LCPUFA) and investigated whether ES affects central and peripheral FA profiles, as well as if and how an early diet with increased availability of ω‐3 LCPUFA ( via lowering ω‐6/ω‐3 ratio) protects against ES‐induced impairments. ES exposure [limited nesting and bedding paradigm from postnatal day (P)2 to P9] altered central and peripheral FA profiles in mice. An early diet with low ω‐6/ω‐3 ratio from P2 to P42 notably prevented the ES‐induced cognitive impairments, and the alterations in hippocampal newborn cell survival and in CD68 + microglia, without affecting the ES‐induced metabolic alterations. Other markers for hippocampal plasticity, apoptosis, and maternal care were unaffected by ES or diet. Our findings highlight the importance of early dietary lipid quality for later cognition in ES‐exposed populations.—Yam, K.‐Y., Schipper, L., Reemst, K., Ruigrok, S. R., Abbink, M. R., Hoeijmakers, L., Naninck, E. F. G., Zarekiani, P., Oosting, A., Van der Beek, E. M., Lucassen, P. J., Korosi, A. Increasing availability of ω‐3 fatty acid in the early‐life diet prevents the early‐life stress‐induced cognitive impairments without affecting metabolic alterations. FASEB J. 33, 5729–5740 (2019). www.fasebj.org